2013
DOI: 10.1126/science.1228605
|View full text |Cite
|
Sign up to set email alerts
|

Comment on "Large Volcanic Aerosol Load in the Stratosphere Linked to Asian Monsoon Transport"

Abstract: Bourassa et al . (Reports, 6 July 2012, p. 78) report on the 13 June 2011 eruption of the Nabro volcano and satellite observations of stratospheric aerosol that they attribute to troposphere to stratosphere ascent via the Asian monsoon. They claim (citing another source) that the 13 June top injection height was well below the tropopause. We will show that the 13 June Nabro eruption plume was clearly stratospheric and contained both volcanic gases and aerosols. Moreover, we will show he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 4 publications
7
43
0
Order By: Relevance
“…(2014) and references therein). While there is some debate regarding the altitude of the plume injection heights (Vernier et al, 2013;Fromm et al, 2013Fromm et al, , 2014, Clarisse et al (2014) suggest that the main injection occurred over altitudes of 15-17 km consistent, with observed plume trajectories, as shown in Bourassa et al (2013). The stratospheric aerosol layer occurred at somewhat higher altitudes (above 18 km; Bourassa et al, 2012;Fairlie et al, 2014), consistent with slow upward transport in the monsoon circulation.…”
Section: Discussion and Summarysupporting
confidence: 60%
“…(2014) and references therein). While there is some debate regarding the altitude of the plume injection heights (Vernier et al, 2013;Fromm et al, 2013Fromm et al, , 2014, Clarisse et al (2014) suggest that the main injection occurred over altitudes of 15-17 km consistent, with observed plume trajectories, as shown in Bourassa et al (2013). The stratospheric aerosol layer occurred at somewhat higher altitudes (above 18 km; Bourassa et al, 2012;Fairlie et al, 2014), consistent with slow upward transport in the monsoon circulation.…”
Section: Discussion and Summarysupporting
confidence: 60%
“…Bourassa et al (2012) have suggested deep convection associated with the Asian monsoon circulation to explain the strong impact of the eruption on the stratospheric aerosol loading. However, this mechanism is controversial after Vernier et al (2013) and Fromm et al (2013) provided satellite evidence for direct injection of the initial Nabro plume into the lower stratosphere.…”
Section: Nabromentioning
confidence: 99%
“…For the present study, we have applied a correction for SO 2 loss using a τ value different for each emission layer. From the decay observed in the total SO 2 mass after the end of the first major injection episode (not shown), we derive an e-folding lifetime of 5 days for the high altitude plumes at 15-18 km (Vernier et al, 2013;Fromm et al, 2013). The e-folding time parameterization as a function of altitude was estimated by interpolation between the values at surface level, taken as 2 days, and the one at 15-18 km (5 days).…”
Section: Inversion Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthering the understanding of the transport of aerosol near and across the tropopause would also benefit from higher spatial and temporal resolution observations. This is evident in the case of volcanic plumes, such as that from Nabro in 2011, the transport and origin of which has been studied extensively and the conclusions are somewhat controversial (Bourassa et al, 2012c(Bourassa et al, , 2013Vernier et al, 2013;Fromm et al, 2013Fromm et al, , 2014Fairlie et al, 2014;Clarisse et al, 2014). However, this is also the case for the formation of background-level aerosol, particularly in the region of the Asian and North American monsoons, which have been identified as a source of substantial, seasonal, and highly structured aerosol formation from precursor tropospheric source gases (Vernier et al, 2011a;Neely et al, 2014;Thomason and Vernier, 2013).…”
Section: Introductionmentioning
confidence: 99%